Bersyukur ala Nanggroe: Intervensi psikososial berbasis indigenous psychology - Johan Satria Putra (Procedia : Studi Kasus dan Intervensi Psikologi, 2015)
The 2004 tsunami disaster in Aceh still remain some psychological impact for the victims. On the other hand, the victims have to possess a preparedness to face similar disasters in the future. Therefore, we need not only a preventive intervention program but also curative. Aceh is a region that has a strong attachment with the local customs and culture. These customs and culture based on the norms of Islam. Based on those culture and religious context, one of many concept may be internalized to the public is ‘gratitude’. Gratitude could bring happiness and well-being within individu. The concept of gratitude derived from western theories generally have a lot of mismatches when applied in the context of local wisdom. Based on this problem, the planned psychosocial intervention program would be oriented to the indigenous psychology, which mainly purposed to create a gratitude training accordingly match with the principles of Aceh local wisdom. The psychosocial intervention consist of four steps. Phase I: Qualitative research using ethnographic methods, to produce an empirical construct of ‘kebersyukuran’ in the Acehnese local communities’ point of view. Later the construct would be used to produce a ‘syukur’ scale and training module. Phase II: Creating intervention program plan and building the team. Phase III : Training. Phase IV: Post-test, evaluation, and monitoring. The target of this intervention is the residents in four villages in Meuraksa and Jaya Baru, Banda Aceh.Keyword : syukur, training, Acehnese indigenous